Hepatoprotective effect of Helicanthus elastica - Sunil Kumar, K. N.; Rajakrishnan, R.; Thomas, J.; Reddy, G. Aadinaath (Bangladesh Journal of Pharmacology, 2016)
Search for medicinal plants to treat liver disorders is an important research topic on herbs. Acute toxicity study is a prerequisite for safety and dose fixation for further pharmacological actions. In the present study, aqueous and 95% ethanolic extract of whole plant of Helicanthus elastica were subjected to acute oral toxicity. The aqueous and ethanolic extract revealed no observable changes in the rats up to the dose level of 2,000 mg /kg body weight. The extracts were then screened for paracetamol-induced hepatic injury at dose levels of 200 and 400 mg/kg body weight (1/10 and 1/5 LD50 based on toxicity study). The aqueous extract of whole plant of H. elastica was found to produce significant (p<0.05) reversal of the paracetamol-induced changes in the measured biochemical and histopathological parameters at lower dose of 200 mg/kg which was found to be better than ethanol extract at the same dose level. Video Clip of Methodology: Acute toxicity study and others: 5 min 38 sec Full Screen Alternate